Is Environmental Training Critical to Environmental Sustainability Behaviour - Aladesanmi, OT; Ogundari, IO; Oladipo, OG; Ilevbare, OE; Ali, GA (International Journal of Environment, 2014)
In the past few decades, concern for the environment has increased significantly with evidences of change in perception of people's values and attitudes towards the environment. This study presents the results of a survey carried out among postgraduate students undergoing training in environmental and non-environmental fields with the aim of comparing their environmental sustainable behaviour. The purpose of the study was to evaluate the impact of environmental training on the postgraduate students? awareness, perceptions and behaviours with focus on the attitudes of the respondents towards environmental sustainability, and how these attitudes affect their behaviour. A purposive sampling method was used to obtain data using a semi-structured questionnaire. The respondents comprised of 50 and 47 postgraduate students undergoing training in environmental and non-environmental respectively. The data was subjected to statistical analysis using SPSS. The results of the study revealed that most of the students in environmental fields readily transferred the knowledge acquired in their training to a sustainable behaviour. DOI: http://dx.doi.org/10.3126/ije.v3i3.11083 International Journal of Environment Vol.3(3) 2014: 241-251